Novel phase change energy storage material and preparation method thereof
By using raw materials such as ammonium chloride, potassium chloride, sodium sulfate, and additives and concentrated agents such as tetraboric acid and sepiolite, new phase change energy storage materials were prepared, which solved the problem of large energy loss in the existing ice cooling technology, achieved the effect of energy storage under positive temperature conditions, and expanded the scope of application.
Patent Information
- Application Number
- CN202510068328.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-16
- Publication Date
- 2025-04-22
AI Technical Summary
In the existing ice cooling technology, ice production is required in negative temperatures, resulting in large energy losses and is difficult to widely use in cooling equipment.
Ammonium chloride, potassium chloride, sodium sulfate as raw materials, combined with tetraboric acid as additives and sepiolite as concentrated agents, new phase change energy storage materials are prepared through specific ratios and preparation methods to achieve the adjustment of the icing temperature.
By designing raw material components with different ratios, phase change energy storage materials with different icing temperatures can be obtained, which achieves the effect of energy storage under positive temperature conditions, expands the application range, and is suitable for cooling and heat storage systems.
Smart Images

Figure CN119859507A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of phase change energy storage materials, and in particular to a novel phase change energy storage material and a preparation method thereof. Background Art
[0002] Phase change material (PCM) refers to a material that changes its state with temperature and can provide latent heat. The process of changing physical properties is called phase change process. At this time, the phase change material will absorb or release a large amount of latent heat. When the physical state changes, the temperature of the material itself remains almost unchanged before the phase change is completed, forming a wide temperature platform. Although the temperature remains unchanged, the latent heat absorbed or released is quite large. Therefore, the functions of phase change materials can be summarized in two points: constant temperature and energy storage, which is also the dual characteristics of phase change materials. In the existing ice storage technology, the phase change material is water. Liquid water and solid ice are converted to each other through heat absorption and heat release to form a phase change process. However, since this technology requires negative temperature ice making (minus 5 degrees), the energy loss is extremely large, which causes great difficulties for the transformation of current equipment that needs cold storage, such as central air conditioning energy storage system, and the cost is high, and it cannot be effectively and widely used. Summary of the invention
[0003] In order to solve the above technical problems, the present application provides a new phase change energy storage material and a preparation method thereof, comprising the following components: 22-25% ammonium chloride, 17-20% potassium chloride, 30-32% sodium sulfate, 8-13% additives, and 15-17% thickener, wherein the additive is disodium tetraborate and the thickener is sepiolite.
[0004] Preferably, the specific ingredients are: 25% ammonium chloride, 20% potassium chloride, 30% sodium sulfate, 8% disodium tetraborate, and 17% sepiolite.
[0005] Preferably, the specific ingredients are: 23% ammonium chloride, 19% potassium chloride, 31% sodium sulfate, 10% disodium tetraborate, and 17% sepiolite.
[0006] Preferably, the specific ingredients are: 23% ammonium chloride, 18% potassium chloride, 31% sodium sulfate, 11% disodium tetraborate, and 17% sepiolite.
[0007] Preferably, the specific ingredients are: 22% ammonium chloride, 19% potassium chloride, 32% sodium sulfate, 11% disodium tetraborate, and 16% sepiolite.
[0008] Preferably, the specific ingredients are: 22% ammonium chloride, 19% potassium chloride, 31% sodium sulfate, 12% disodium tetraborate, and 16% sepiolite.
[0009] Preferably, the specific ingredients are: 23% ammonium chloride, 17% potassium chloride, 32% sodium sulfate, 13% disodium tetraborate, and 15% sepiolite.
[0010] Preferably, a preparation method for preparing the above-mentioned novel phase change energy storage material comprises the following steps:
[0011] S1. The four raw materials of ammonium chloride, potassium chloride, sodium sulfate and thickener are weighed and mixed according to the proportion, and each raw material is divided into several portions;
[0012] S2. Boil the water in the boiling tank to 65-70℃, add the first portion of ammonium chloride into the tank, wait for 5-8 minutes, then add the first portion of potassium chloride, wait for 10-12 minutes, then add the first portion of sodium sulfate, wait for 5-8 minutes, then add the first portion of thickener, and wait for 10-12 minutes;
[0013] S3. After completing step S2, continue to pour the second portion of each raw material into the tank according to the feeding order and waiting time of step S2 until all the raw materials are poured into the tank;
[0014] S4. After the last portion of thickener is poured into the tank, wait for 10-12 minutes, pour the additives into the tank at once, and wait for the materials in the tank to react with each other for 30-35 minutes;
[0015] S5. Pour the material in the cylinder into a container for canning and sealing. After sealing, transfer it to a heating room for heating and let it stand for 9-10 hours at a heating temperature of 45-50℃.
[0016] Preferably, in step S2, the pouring time of ammonium chloride, potassium chloride and thickener does not exceed 10 minutes, and the pouring time of sodium sulfate does not exceed 15 minutes.
[0017] Preferably, the method further includes a testing step: transferring the heated and stationary container to a low-temperature environment and placing it for more than 12 hours to allow the material in the container to freeze for the first time, leaving the low-temperature environment and allowing it to stand at room temperature for the first cooling and thawing, then performing a second freezing and a second cooling and thawing, and transferring the material in the container to an instrument for quality testing.
[0018] From the above, it can be seen that the application provided by the present application can obtain the following beneficial effects: by designing different ratios of the raw material components, phase change energy storage materials with different freezing temperatures can be obtained, and the present scheme obtains a phase change energy storage material with a positive freezing temperature, and the raw materials and processes used in the prior art can only obtain a phase change material of a certain temperature. The present scheme adopts ammonium chloride, potassium chloride, and sodium sulfate as raw materials, cooperates with disodium tetraborate as an additive and uses sepiolite as a thickener, and then prepares the phase change energy storage material through the above-mentioned preparation method. By designing different ratios of the raw material components, phase change energy storage materials with different freezing temperatures can be obtained. They can be used not only in cold storage systems, but also in heat storage systems, and have a wide range of uses. Compared with phase change materials with a single temperature specification, the phase change energy storage materials and preparation methods of the present scheme have broader application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] In order to more clearly illustrate the technical solutions in the embodiments of the present application or the prior art, the drawings required for use in the description of the embodiments of the present application or the prior art are briefly introduced below. Obviously, the drawings described below are only part of the embodiments of the present application, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative labor.
[0020] Figure 1 This is a flowchart of the method for preparing a new phase change energy storage material according to an embodiment of the present application. DETAILED DESCRIPTION
[0021] The technical solutions in the embodiments of the present application will be described clearly and completely below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.
[0022] Example 1
[0023] In order to solve the above technical problems, this embodiment provides a new phase change energy storage material, including the following components: 22-25% ammonium chloride, 17-20% potassium chloride, 30-32% sodium sulfate, 8-13% additives, and 15-17% thickeners, wherein the additive is disodium tetraborate and the thickener is sepiolite.
[0024] Preferably, the specific ingredients are: 25% ammonium chloride, 20% potassium chloride, 30% sodium sulfate, 8% disodium tetraborate, and 17% sepiolite.
[0025] On the other hand, this embodiment provides a preparation method for preparing the above-mentioned novel phase change energy storage material, such as Figure 1As shown, the following steps are included:
[0026] S1. The four raw materials of ammonium chloride, potassium chloride, sodium sulfate and thickener are weighed and mixed according to the proportion, and each raw material is divided into several portions;
[0027] In this step, since the viscosity of ammonium chloride is relatively high, it is necessary to first add the ammonium chloride into a mixing tank and crush it, stir the crushed ammonium chloride for 0.5 hours, and then pack it into a plastic barrel after stirring evenly. In this scheme, the four raw materials of ammonium chloride, potassium chloride, sodium sulfate, and thickener are respectively packaged into 5 portions.
[0028] S2. Boil the water in the boiling tank to 65-70℃, add the first portion of ammonium chloride into the tank, wait for 5-8 minutes, then add the first portion of potassium chloride, wait for 10-12 minutes, then add the first portion of sodium sulfate, wait for 5-8 minutes, then add the first portion of thickener;
[0029] In step S2, first boil 500L of water to 65°C, add the first portion of ammonium chloride into the tank, wait for 5 minutes and then pour in the first portion of potassium chloride, wait for 10 minutes and then pour in the first portion of sodium sulfate, wait for 5 minutes and then pour in the first portion of thickener, and wait for 10-12 minutes.
[0030] Among them, the above raw materials are poured slowly to improve the uniformity of mixing, and the pouring time of ammonium chloride, potassium chloride and thickener shall not exceed 10 minutes, and the pouring time of sodium sulfate shall not exceed 15 minutes.
[0031] S3. After completing step S2, continue to pour the second portion of each raw material into the tank according to the feeding order and waiting time of step S2 until all the raw materials are poured into the tank;
[0032] After pouring the first batch of raw materials, wait for 10 minutes, and continue to pour the second batch of raw materials into the tank according to the order of feeding and waiting time in step S2 until all the raw materials are poured into the tank.
[0033] S4. After the last portion of thickener is poured into the tank, wait for 10-12 minutes, pour the additives into the tank at once, and wait for the materials in the tank to react with each other for 30-35 minutes;
[0034] S5. Pour the material in the cylinder into a container for canning and sealing. After sealing, transfer it to a heating room for heating and let it stand for 9-10 hours at a heating temperature of 45-50℃.
[0035] By designing the above-mentioned feeding sequence and feeding time, the efficiency of the interaction reaction of the materials in the cylinder is improved, and finally a phase-change energy storage material with uniform mixed phase is obtained. Among them, the phase-change energy storage material with a freezing temperature of 8°C is prepared by the above-mentioned formula and process.
[0036] Furthermore, it also includes a testing step: transferring the heated and stationary container to a low temperature environment for more than 12 hours, so that the material in the container freezes for the first time, leaving the low temperature environment and standing at room temperature for the first cooling and thawing, waiting for the phase change energy storage material in the container to completely recover to a semi-fluid state, indicating that the contained cold has been completely released, and then performing the second freezing and the second cooling and thawing, and transferring the material in the container to the instrument for quality testing. Among them, the temperature of the low temperature environment is 3-4°C lower than the freezing temperature of the phase change energy storage material.
[0037] Example 2
[0038] The specific ingredients of the phase change energy storage material of this embodiment are: 23% ammonium chloride, 19% potassium chloride, 31% sodium sulfate, 10% disodium tetraborate, and 17% sepiolite. The preparation method is the same as that of Example 1. The phase change energy storage material with a freezing temperature of 10°C is prepared by the above formula and process.
[0039] Example 3
[0040] The specific composition of the phase change energy storage material of this embodiment is: 23% ammonium chloride, 18% potassium chloride, 31% sodium sulfate, 11% disodium tetraborate, and 17% sepiolite, and the preparation method is the same as that of Example 1. The phase change energy storage material with a freezing temperature of 13°C is prepared by the above formula and process.
[0041] Example 4
[0042] The specific composition of the phase change energy storage material of this embodiment is: 22% ammonium chloride, 19% potassium chloride, 32% sodium sulfate, 11% disodium tetraborate, and 16% sepiolite, and the preparation method is the same as that of Example 1. The phase change energy storage material with a freezing temperature of 15°C is prepared by the above formula and process.
[0043] Example 5
[0044] The specific composition of the phase change energy storage material of this embodiment is: 22% ammonium chloride, 19% potassium chloride, 31% sodium sulfate, 12% disodium tetraborate, and 16% sepiolite, and the preparation method is the same as that of Example 1. The phase change energy storage material with a freezing temperature of 17°C is prepared by the above formula and process.
[0045] Example 6
[0046] The specific composition of the phase change energy storage material of this embodiment is: 23% ammonium chloride, 17% potassium chloride, 32% sodium sulfate, 13% disodium tetraborate, and 15% sepiolite, and the preparation method is the same as that of Example 1. The phase change energy storage material with a freezing temperature of 19°C is prepared by the above formula and process.
[0047]
[0048]
[0049] Table 1
[0050] Table 1 is a table showing the relationship between the component ratios and the freezing temperatures of various embodiments. It can be seen from Table 1 that phase change energy storage materials with different freezing temperatures can be obtained by designing different ratios of the raw material components, and the present solution obtains a phase change energy storage material with a positive freezing temperature. The raw materials and processes used in the prior art can only obtain phase change materials with a certain temperature. The present solution uses ammonium chloride, potassium chloride, and sodium sulfate as raw materials, and uses sodium tetraborate as an additive and sepiolite as a thickener, and then prepares the phase change energy storage material through the above-mentioned preparation method. By designing different ratios of the raw material components, phase change energy storage materials with different freezing temperatures can be obtained. The phase change energy storage materials can be used not only in cold storage systems, but also in heat storage systems, and have a wide range of uses. Compared with phase change materials with a single temperature specification, the phase change energy storage materials and preparation methods of the present solution have broader application prospects.
[0051] The above-described implementation methods do not constitute a limitation on the protection scope of the technical solution. Any modification, equivalent replacement and improvement made within the spirit and principle of the above-described implementation methods shall be included in the protection scope of the technical solution.
Claims
1. A new phase change energy storage material, characterized in that: The invention comprises the following ingredients: 22-25% ammonium chloride, 17-20% potassium chloride, 30-32% sodium sulfate, 8-13% additives and 15-17% thickener, wherein the additive is disodium tetraborate and the thickener is sepiolite.
2. The novel phase change energy storage material according to claim 1, characterized in that: The specific ingredients are: 25% ammonium chloride, 20% potassium chloride, 30% sodium sulfate, 8% disodium tetraborate, and 17% sepiolite.
3. The novel phase change energy storage material according to claim 1, characterized in that: The specific ingredients are: 23% ammonium chloride, 19% potassium chloride, 31% sodium sulfate, 10% disodium tetraborate, and 17% sepiolite.
4. The novel phase change energy storage material according to claim 1, characterized in that: The specific ingredients are: 23% ammonium chloride, 18% potassium chloride, 31% sodium sulfate, 11% disodium tetraborate, and 17% sepiolite.
5. The novel phase change energy storage material according to claim 1, characterized in that: The specific ingredients are: 22% ammonium chloride, 19% potassium chloride, 32% sodium sulfate, 11% disodium tetraborate, and 16% sepiolite.
6. The novel phase change energy storage material according to claim 1, characterized in that: The specific ingredients are: 22% ammonium chloride, 19% potassium chloride, 31% sodium sulfate, 12% disodium tetraborate, and 16% sepiolite.
7. The novel phase change energy storage material according to claim 1, characterized in that: The specific ingredients are: 23% ammonium chloride, 17% potassium chloride, 32% sodium sulfate, 13% disodium tetraborate, and 15% sepiolite.
8. A preparation method, characterized in that: The method for preparing the novel phase change energy storage material according to any one of claims 1 to 7 comprises the following steps: S1. The four raw materials of ammonium chloride, potassium chloride, sodium sulfate and thickener are weighed and proportioned according to the proportion, and each raw material is divided into several portions; S2. Boil the water in the boiling tank to 65-70℃, add the first portion of ammonium chloride into the tank, wait for 5-8 minutes, then add the first portion of potassium chloride, wait for 10-12 minutes, then add the first portion of sodium sulfate, wait for 5-8 minutes, then add the first portion of thickener, and wait for 10-12 minutes; S3. After completing step S2, continue to pour the second portion of each raw material into the tank according to the feeding order and waiting time of step S2 until all the raw materials are poured into the tank; S4. After the last portion of thickener is poured into the tank, wait for 10-12 minutes, pour the additives into the tank all at once, and wait for the materials in the tank to react with each other for 30-35 minutes; S5. Pour the material in the cylinder into a container for canning and sealing. After sealing, transfer it to a heating room for heating and let it stand for 9-10 hours at a heating temperature of 45-50℃.
9. The preparation method according to claim 8, characterized in that: In step S2, the pouring time of ammonium chloride, potassium chloride and thickener shall not exceed 10 minutes, and the pouring time of sodium sulfate shall not exceed 15 minutes.
10. The preparation method according to claim 8, characterized in that: The detection step is also included: transferring the heated and stationary container to a low-temperature environment and placing it for more than 12 hours to allow the material in the container to freeze for the first time, leaving the low-temperature environment and allowing it to stand at room temperature for the first cooling and thawing, and then freezing and thawing for the second time, and transferring the material in the container to the instrument for quality testing.
Citation Information
Patent Citations
Cold-chain transportation phase change material and preparation method thereof
CN103756645A
Phase-change material used for air conditioning and processing technology thereof
CN108504335A
Cold storage material for air conditioners
CN109251731A
Phase change material with two phase-transition temperatures and preparation method thereof
CN110257020A
Composite eutectic salt phase change cold storage material and preparation method thereof
CN114854374A